Climate Smart Village project: How can farmers use laser land leveling to improve food production? - CGIAR Research Program on Climate Change, Agriculture and Food Security (2013)
CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS) has introduced the model of "Climate Smart Villages (CSVs)" in India, and is slowly scaling up and expanding to other countries in the South Asia region. www.ccafs.cgiar.org The idea is to raise awareness among farming communities in South Asia about various technological, institutional and policy-oriented options that have the potential to increase their climatic resilience, adaptation, agricultural productivity and income, while reducing emissions of greenhouse gases. In this video, you will learn more about the benefits from Laser Land Leveling. Read more: http://ow.ly/kXVFR